PENERAPAN MODEL THINK TALK WRITE UNTUK MENINGKATKAN KETERAMPILAN SISWA DALAM MENULIS KARANGAN DESKRIPSI DI SEKOLAH DASAR - Panji Maulana; MT Hartono Ikhsan (Jurnal Pesona Dasar, 2018)
The results of the Program for International Student Assessment (PISA) study stated that literacy culture (the ability to read and write) the Indonesian people in 2012 was the second worst of 65 countries studied in the world. The problem in this study is the low learning activities and writing skills of fourth grade students of Cimanggung Elementary School, Cimanggung District, Sumedang Regency. This study aims to determine the increase in student learning activities, teacher teaching activities, and essay writing skills of grade IV students using Think Talk Write models. The instruments used in this study are observation sheets of student learning activities, observation sheets of teacher activities, and tests. The purpose of this study is to improve the ability to write essays and student learning activities, describe the steps and process / implementation of writing essay learning by applying TTW learning models (Think Talk Write), and describe whether there is an increase in the ability to write essays by applying TTW learning models (Think Talk Write) on fourth grade students of SDN Cimanggung, Cimanggung District, Sumedang Regency. The research method used is Classroom Action Research with a research design used referring to a model developed by Kemmis and Taggart, namely a spiral model that starts with: 1) planning; 2) acting / acting; 3) observation (observing); and 4) reflecting. The research subjects were 30 grade IV students of SDN Cimanggung, consisting of 15 women and 15 men. This research was conducted for 2 cycles.